Admixture Effects on Coevolved Metabolic Systems - Zascavage, Roxanne R.; Planz, John V. (Frontiers in Genetics, 2018)
Oxidative phosphorylation (OXPHOS) is the primary energy generating system in eukaryotic organisms. The complexes within the OXPHOS pathway are of mixed genomic origin. Although most subunit-coding genes are located within the nuclear genome, several genes are coded for in the mitochondrial genome. There is strong evidence to support coadaptation between the two genomes in these OXPHOS gene regions in order to create tight protein interactions necessary for a functional energetics system. In this study, we begin to assess the physiological impact of separating coevolved protein motifs that make up the highly conserved energy production pathway, as we hypothesize that divergent matings will significantly diminish the protein interactions and therefore hinder efficient OXPHOS activity We measured mitochondrial activity in high energy-demanding tissues from six strains of Mus musculus with varying degrees of mixed ancestral background. Mice with divergent mitochondrial and nuclear backgrounds consistently yielded lower mitochondrial activity. Bioinformatic analysis of common single nucleotide variants across the nuclear and mitochondrial genomes failed to identify any nonsynonymous variants that could account for the energetic differences, suggesting that interpopulational mating between ancestrally distinct groups influences energy production efficiency.